Therapeutic Occupation Activities - Nursing Structured Interventions in Psychosocial Rehabilitation [Póster] - Dias, Carlos Manuel de Melo (2015)
INTRODUCTION In its therapeutic dimension associated with the treatment of people with mental illness, occupation started being understood as a continuous adaptive process which allows individuals to develop skills, competencies and their own identity. The process of psychosocial rehabilitation and recovery has the intrinsic goal of teaching and training mentally impaired individuals to perform the physical, emotional and intellectual skills needed for leading an autonomous life. OBJECTIVE This theoretical essay aims to propose the concept of Therapeutic Occupational Activity (TOA) in Nursing, while establishing a specific dynamics between its three core elements, nurse-client-activity, as well as with its fields of use. DEVELOPMENT & ESSAY The Therapeutic Occupation Activities (TOAs) are defined as systematic and organized activities that structure and guide the functional performance of the participant within the interpersonal nurse-client relationship and the assessment of the Fundamental Human Needs (FHN). Nurses make use of therapeutic techniques which are selected and prescribed according to the intended objective(s), with psychotherapeutic, psychoeducational, psychomotor, psychosocial, socio-therapeutic and spiritual consequences. They aim to promote, prevent, empower, maintain and/or recover and develop the individual's skills so as to reach their maximum potential for performance, autonomy and satisfaction of their FHN, daily activities, and occupation for achievement and recreation. Implies a scientific intervention and requires excellent interpersonal skills, knowledge of the cognitive-behavioral therapies, enthusiasm with work, resilience to perform thorough procedures with negligible/minor situational feedbacks and also the ability to use feedback and feedforward processes. The Autonomous Nursing clinical practice is focused on the interpersonal/therapeutic relationship between a nurse and an individual/group. Are identified tree types of participants skills: Receptive Skills (to interpret relevant cues or signals efficiently); Processing Skills (to assess the information received, the objectives and the planning of a behavioral response); Sending Skills (adequate verbal, non-verbal and paralinguistic behaviors). The human responses to development and disease processes, and also the length and type of hospital stay, the cultural and demographic characteristics, the life projects and expectations, the disruptions caused by the new roles, the pain and the (physical, mental and social) suffering, the adaptation difficulties, and the cognitive impairment have a general and specific influence on the design of nursing interventions in TOAs. Also, the Nurse, as leader and rater is in a position of co-territoriality, because is emotionally and rationally integrated in the situation, while maintaining a technical distance. Key features of TOAs Goal-oriented + Consistency with the daily life + Engages and unites + Prescription by Nurses + Gradual and adapted + Informed Consent + add value for the client + towards participant's satisfaction and personal and social functioning. Determinants of TOAs in mental health and psychiatric nursing Stigma, Standards and Philosophy of Care, Nurses' Motivation, Funding Difficulties, Emotional and Behavioral Deficits, Impaired Communication Skills, and Learning difficulties. Fields of use of TOAs Clinically relevant in: Personal and Domestic, Recreation and Leisure, Self-Expression, Psychoeducation, Health Education and Interpersonal Relationships. The therapeutic indications for prescribing TOAs are: a) Maintenance of the maximum level of well-being; b) Promotion of biopsychosocial functions; c) Promotion of social adaptation/integration; d) Implementation of recovery/rehabilitation; e) Assessment of clinical situations: deficits, disabilities; f) Prevention of cognitive-behavioral decline; g) Prevention of an extended hospital stay and the "revolving-door" phenomenon. Benefits of TOAs in mental health and psychiatric nursing • Promotion of behavioral organization • Sense of social utility • Building self-esteem and self-image • Resocialization • Reduction of inappropriate behaviors • Prevention of the overall physical and cognitive decline • Construction of a rewarding image of the Nurse Conclusion Therapeutic Occupation Activities emphasizes the person at the center of the decision, participation taking place in clinical nursing environment, based on the Fundamental Human Needs, dealing with problems/focus of attention of nursing, and is therefore prescribed, implemented and evaluated by nurses, according to the clinical nursing reasoning and diagnoses. The TOAs are a key therapeutic tool for the Nurse in MHPN toward the prevention of morbidity and the promotion of readaptation process as crucial outcomes, with the benefits on improved functioning, on decreased duration of hospitalizations and costs savings of all inpatient that had participated. We recognize the method as reproducible and it is possible to build knowledge, and even assuming its appetence for generalization of effects and results in natural environments of clients.